2014
DOI: 10.1002/2014ja019790
|View full text |Cite
|
Sign up to set email alerts
|

Polar summer mesospheric extreme horizontal drift speeds during interplanetary corotating interaction regions (CIRs) and high‐speed solar wind streams: Coupling between the solar wind and the mesosphere

Abstract: We report the observation of echo extreme horizontal drift speed (EEHS, ≥ 300 m s À1 ) during polar mesospheric (80-90 km) summer echoes (PMSEs) by the VHF (52 MHz) radar at Esrange, Sweden, in years of 2006 and 2008. The EEHS occur in PMSEs as correlated with high-speed solar wind streams (HSSs), observed at least once in 12-17% of all hours of observation for the two summers. The EEHS rate peaks occur either during high solar wind speed in the early part of the PMSE season or during the arrival of interplane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Thus, PMSE and AE peaks usually precede solar wind speed peaks as reported in Lee et al . [, ]. Detailed relative timing of these events is not properly represented when we have used filtered time series to separate 7 day and 9 day periodicities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PMSE and AE peaks usually precede solar wind speed peaks as reported in Lee et al . [, ]. Detailed relative timing of these events is not properly represented when we have used filtered time series to separate 7 day and 9 day periodicities.…”
Section: Resultsmentioning
confidence: 99%
“…Using magnetic disturbance indices such as K, Kp, Ap, and AE, a clear influence on PMSE has been found, although varying from year to year [Bremer et al, 2000;Barabash et al, 2002;Zeller and Bremer, 2009;Kirkwood et al, 2013;Smirnova et al, 2011]. Recently, it has been found that high-speed solar wind stream (HSS)-induced geomagnetic disturbances are likely followed by an increased production of PMSE [Lee et al, 2013[Lee et al, , 2014. The HSS-differentiated effect on PMSE is attributed to a large increase in high-energy electrons and relativistic electrons penetrating into the polar middle atmosphere during HSS [e.g., Baker et al, 1987;Rostoker et al, 1998;Meredith et al, 2011;Newnham et al, 2011;Kavanagh et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Moving forward, charge separation can be developed in the transition from PMSE to PMC. Extreme plasma drift speed of ≥300 m s −1 and supersonic velocity bring forth wind shear in PMSE/PMC regions, leading to Kelvin‐Helmholtz instability [e.g., Lee et al ., ; Mann et al ., ; Dalin et al ., ]. Wind shear is an important measure of the potential of squall line severity, which is usually associated with thunderstorms [ Rotunno and Klemp , ], since charge separation, squall, breakdown, and leader discharge of lightning are the consequential process in the tropospheric thunderclouds [ Rotunno and Klemp , ].…”
Section: Production Mechanism Of Sb‐accompanied Summer Intense Emissionmentioning
confidence: 99%
“…The summer dayside FUV aurora might be related with high‐energy electron precipitation induced by whistler mode chorus wave, which is still active even at geomagnetically quiet times although electron precipitation flux is greatly decreased and the observed altitude is still uncertain [ Li et al ., ]. Nonetheless, extreme plasma drift speed (300–1400 m s −1 ) was observed in PMSE by radar with a competitive effect by either the solar wind speed or the dynamic pressure enhancement induced by HSSs [ Lee et al ., ]. Due to the high neutral density below 90 km, the ions are only forced by the electric field and not by the magnetic field [ Heelis , ].…”
Section: Production Mechanism Of Sb‐accompanied Summer Intense Emissionmentioning
confidence: 99%
“…In particular we examine the relationship with high-speed solar wind streams (HSS) since these have recently been shown to have a strong influence on VHF radar echoes during some summer periods (Lee et al, 2013(Lee et al, , 2014. High-energy electron precipitation associated with the arrival of HSS at the Earth has been well documented and is expected to lead to significant ionization at PMWE heights at the location of Troll (e.g.…”
Section: S Kirkwood Et Al: Antarctic Pmwe During Hssmentioning
confidence: 99%